Feruloyl esterase from Aspergillus clavatus improves xylan hydrolysis of sugarcane bagasse - Dyoni M. de Oliveira; Victor Hugo Salvador; Thatiane R. Mota; Aline Finger-Teixeira; Rodrigo F. de Almeida; Douglas A. A. Paixão; Amanda P. De Souza; Marcos S. Buckeridge; Rogério Marchiosi; Osvaldo Ferrarese-Filho; Fabio M. Squina; Wanderley D. dos Santos (AIMS Bioengineering, 2016)
Feruloyl esterase is a subclass of carboxylic acid esterases with the capacity to release ferulic acid and other cinnamic acids from plant cell walls and synthetic substrates. Feruloyl esterases act synergistically with xylanases removing ferulic acid residues esterified to arabinoxylans. Feruloyl esterase type D from Aspergillus clavatus (AcFAE) was expressed in Escherichia coli, purified, and applied with a commercial xylanase consortium (Novozymes) for hydrolysis of sugarcane bagasse. Feruloyl esterase plus xylanase increased 5.13-fold the releasing of ferulic acid from sugarcane bagasse. Removal of only 7.7% of ferulic acid content by AcFAE increased 97.3% the sugarcane bagasse hydrolysis by xylanase. These data support the use of AcFAE as an interesting adjuvant enzyme to improve lignocellulose digestion and biotechnological tool for biorefineries.